Sex Differences and Estrous Cycle Changes in Synaptic Plasticity-related microRNA in the Rat Medial Amygdala. (21st May 2018) - Hirsch, Mauro Mozael; Brusco, Janaína; Vaccaro, Tamara; Margis, Rogerio; Moreira, Jorge E.; Gottfried, Carmem; Rasia-Filho, Alberto A.
Highlights: microRNA interferes with neuronal structure and synaptic plasticity in the amygdala. Males have higher levels of miR138 and miR-181a than females along the estrous cycle. Males have lower levels of miR-132 and miR-199a than proestrus females. Diestrus females have higher levels of miR-25 than proestrus females. Diestrus females have higher values of miR-25, miR-181a and miR-195 than estrus females. Abstract: The posterodorsal medial amygdala (MePD) is a sex steroid-sensitive and sexually dimorphic subcortical area that dynamically modulates social behaviors in rats. As different microRNA (miRNA) can act as post-transcriptional regulators of synaptic processing, we addressed changes that occur in miRNA expression in the MePD of males and females along the estrous cycle. The expression of miR25-3p, miR132-3p, miR138-5p, miR181a-5p, miR195-5p, and miR199a-5p, involved in neuronal cytoskeleton remodeling and synaptic plasticity, were evaluated by RT-qPCR. We found that the expression of miR138-5p was higher in males than in females along the different phases of the estrous cycle. Males also showed higher levels of miR-181a when compared to females in diestrus and estrus. On the other hand, when compared to females in proestrus, males presented lower levels of miR132-3p and miR199a-5p. The expression of miR25-3p was higher in diestrus females than in proestrus females. In addition, diestrus females showed higher values of miR25-3p, miR181a-5p, and miR195-5p when compared to estrus females. These miRNA expression profiles indicate a variable and fine-tuned protein regulation in the adult MePD. It is likely that these miRNA can be involved in structural and functional synaptic features and plasticity characteristic of males and cycling females and for the MePD regulation of mammalian reproduction.